The Effect of Using E-Learning on improving Vocabulary and Grammar Skills among Academic English Language Students (Journal of the College of Basic Education, 2023)
In the 21st century, the advancement of technology plays essential role in the field of education and schooling. The term e-learning refers to electronic learning which an alternative of the traditional education system is.Subjects and methods:In this study, eighty four second stage EFL students at College of Arts, AL Mustansiriyha University randomly allocated into two groups. The first group (n=43) received New words of the English textbook without using E-Learning. The second group (n=41) involved the use of E- Learning to enhance vocabulary and grammar skills for the same period and served as the interventional group. This study adopted (pretest- posttest).. After the end of the tests,; the results have been analyzed.ResultsThe researcher compared the mean score of the EG (45.302) and that of the CG (41.024). By utilizing the t-test formula for two independent samples, it has found that the computed t-value is 3.376, which is higher than the tabulated t-value (1.99), at the 0.05 level of significance and 82 degrees of freedom. That indicates there is a statistically significant difference between the two groups in favor of the EG.ConclusionThe use of E- Learning could enhance vocabulary and Grammar skills in Iraqi universities English students.